Business ethics: A connection to good corporate governance implementation - Sambas Ade Kesuma; Risanty Risanty; Muhammad Husni Mubarok; Citra Marisa (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The main purpose of this study is to discuss business ethics and good corporate governance implementation. Business ethics is the foundation of good corporate governance implementation in a company. The existence of ethics in the company is expected to be a benchmark for measuring moral values, especially policies. It is also expected that the application of good business ethics elevates the implementation of good corporate governance. The establishment of supervisory institutions in public sector organizations is also expected to be the best way to eliminate the ethical violation. Thus, good business practices and the environment in Indonesia can be achieved.